Histories of ornament from global to local - Necipoglu, Gulru; Payne, Alina (Princeton University Press, 2016)
"This lavishly illustrated volume is the first major global history of ornament from the middle ages to today. Crossing historical and geographical boundaries in unprecedented ways and considering the role of ornament in both art and architecture, Histories of Ornament offers a nuanced examination with their Islamic, Indian, Chinese and Mesoamerican counterparts. At a time when ornament has re-emerged in architectural practice and is a topic of growing interest to art and architectural historians, the book reveals how the long history of ornament illuminates its global resurgence today." -- Provided by publisher